Secular humanitarians and the postsecular: reflections on Habermas and the Typhoon Haiyan disaster response. Issue 2 (4th May 2018) - Wilkinson, Olivia
Abstract: The international humanitarian system aims to save lives and alleviate suffering following disasters worldwide. Secular and faith-based actors make up the system, but the system can operate to a secular standard that may, some have argued, marginalise religious experience and well-being post-disaster. This article assesses what can be learned from examining secular humanitarianism from a postsecular perspective. Debate on secularity in the humanitarian system is reviewed, before Jürgen Habermas's conception of the postsecular is proposed as a theoretical lens. Habermasian postsecularism invites the secular to take part in a process of 'complementary learning' with the religious. Results from interviews and focus groups in the Philippines following Typhoon Haiyan are used. Results show the reflexivity of secular individuals within the humanitarian system, with cases demonstrating co-operation and consideration of other views at the interpersonal level. Yet, at a system-wide level, instances of marginalisation of religion were noted, such as responses to requests for chapel reconstruction and psycho-social assistance. While some organisations made a contextualised decision that either maintained their strict secularity or negotiated a compromise, in other cases, these decisions were based on preconceptions rather than deliberation. Overall, a level of reflexivity required in Habermasian postsecularism was found, but there were also further opportunities for complementary learning.